Homo Reciprocans Revisited - Jin Di Zheng (Tinbergen Institute, 2017)
Do reciprocal workers work more if their wage compares well to similar workers in the economy? Are they more satisfied with their job? Predictions vary from theories. With a survey dataset with a representative sample of the German population, I construct a reference wage and measures for reciprocity for each worker. Depending on how much more or less a worker earns than the reference, I investigate how effort and job satisfaction react to reciprocity tendencies. The results suggest that a worker's unpaid overtime hours increase with her relative earnings if above the reference; and the more so, the stronger her positive reciprocity tendency is. However, there is no such interaction for negative reciprocity. Job satisfaction is associated with reciprocity, yet insensitive to the interaction between reciprocity and relative income.
Keywords: J3; M5; 330; reciprocity; effort; satisfaction; reference wage